TEACHING EFL LEARNERS THE PAST PERFECT AND PAST SIMPLE THROUGH COGNITIVE GRAMMAR: EXPERIMENTAL EVIDENCE - Hidarto, Anderson (LLT Journal: A Journal on Language and Language Teaching, 2018)
Cognitive Grammar (CG) is a relatively new approach to linguistics that is becoming more mainstream in recent years due to its comprehensive description and meaningful elaboration of grammar. CG proponents have been proposing this approach to L2 grammar instruction instead of a more traditional approach that relies heavily on rules. Our main interest is to investigate whether such approach is indeed beneficial to learners, particularly in the learning of English past tenses. Our goal in the current study is therefore to examine the relative effect of CG instruction on Indonesian EFL learnersâ mastery of two past tenses, simple past and past perfect. These tenses were selected as our instructional targets since most common traditional explanation does not help learners differentiate and use them contextually (Jones & Lock, 2011). Twenty-seven EFL learners studying at a senior high school in Jakarta participated in this quasi-experimental study. They were assigned to one experimental group receiving a two-week pedagogical treatment with pre-test and immediate post-test design. Statistical analyses indicate that the group significantly performed better after the treatment, notably in discourse-related test sections. The results confirm the efficacy of CG which can lend support to its applications in L2 instruction.DOI:Â doi.org/10.24071/llt.2018.210211